If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = 4(-2x + -6) Reorder the terms: 16 = 4(-6 + -2x) 16 = (-6 * 4 + -2x * 4) 16 = (-24 + -8x) Solving 16 = -24 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 16 + 8x = -24 + -8x + 8x Combine like terms: -8x + 8x = 0 16 + 8x = -24 + 0 16 + 8x = -24 Add '-16' to each side of the equation. 16 + -16 + 8x = -24 + -16 Combine like terms: 16 + -16 = 0 0 + 8x = -24 + -16 8x = -24 + -16 Combine like terms: -24 + -16 = -40 8x = -40 Divide each side by '8'. x = -5 Simplifying x = -5
| -25-4(2x+5)=-61 | | 4c+5y-6z=2 | | -3x-3n=x | | -16=2(z) | | 3-9=-3-13 | | bx+4=-12 | | m+4(m+3)=28 | | 4a-2a-18=6 | | 12+w+12+w=44 | | 2.66/9.50= | | 7x+3=4-(9x-3) | | -6n-4n= | | 0.2(3x-4)=2(19.7+7x) | | 18-3-x=2-x+3 | | 5(-2x+4)=0 | | 2(y+3)=2 | | F(2)=15x+4 | | X+60=120 | | 10m-0=12 | | h-3h=0 | | (12+w)(w)=44 | | x*4+3=11 | | 7x+8=8+7x | | (12+w)(w)=-44 | | 7h-(15)=48 | | 3x-7+4(x+1)=2x-4 | | 2d(3)= | | 96=-4(3+3x) | | 9(c)=-99 | | 30n^7y^2t+12n^4t^5= | | -3(k-6)=-3(k-2)-3 | | x/5=3x-2/4 |